Physical conditioning of U16 national team players: Mediator effect of previous sport experiences and strength and conditioning practices - Arede, J.; Esteves, P.; Ferreira, A. P.; Leite, N. (Journal of Human Sport & Exercise, 2019)
The aims of this study were (a) to investigate the effects of previous strength and conditioning in physical performance; (b) to examine the mediator effect of previous sport experiences in physical performance, according to the training group (c) to examine the relationship between training frequency and physical performance. Twenty-four young under-16 (U-16) male basketball players performed several physical (jumping, sprinting, and change-of-direction speed) and functional (ankle dorsiflexion and lower limb asymmetry index [ASI]) tests during the national team training camp. Previous sport experiences, and strength and conditioning practices in club settings were collected using customized questionnaires. Cluster analysis was used to analyse the between strength and conditioning practices status differences (Group 1 and 2) in physical and functional parameters. No significant differences were found between groups, in physical and functional parameters. However, we found a significant main effect of non-specific deliberate practice in T-test, right ankle dorsiflexion and ankle dorsiflexion symmetry. Also, the ASI and strength/power training frequency were significantly related. Early non-specific deliberate practice and strength/power sessions involvement seem to play a key role on the development of the neuromuscular system and injury prevention.